1991
DOI: 10.1016/0248-4900(91)90067-w
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoa and relationships in palaeognath birds

Abstract: In this paper the authors describe the ultrastructure of the mature spermatozoon and the spermatid in Struthio camelus and Dromaius novaehollandiae. The first species is characterized by a rod-like perforatorium within an endonuclear canal in the anterior third of the nucleus, while the second is characterized by an extremely reduced completely extranuclear perforatorium. Other differences are in the sperm dimensions, the number of mitochondria and the length of the axonemal accessory fibers. Considering both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
53
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 7 publications
(13 reference statements)
16
53
1
1
Order By: Relevance
“…Conventional SEM confirmed the basic morphological features of emu sperm previously observed by light microscopy [16] and SEM [12]. The cells were long and narrow and the various segments, namely, the acrosome, nucleus, midpiece, principal piece and endpiece, could be distinguished although the transition was not always clear (Fig.…”
Section: Scanning Electron Microscopysupporting
confidence: 82%
See 4 more Smart Citations
“…Conventional SEM confirmed the basic morphological features of emu sperm previously observed by light microscopy [16] and SEM [12]. The cells were long and narrow and the various segments, namely, the acrosome, nucleus, midpiece, principal piece and endpiece, could be distinguished although the transition was not always clear (Fig.…”
Section: Scanning Electron Microscopysupporting
confidence: 82%
“…The SEM data of Baccetti et al [12] provides little information on the surface morphology of emu sperm other than to note the length of the various segments of the cell and that the midpiece is not as "deeply marked as in the ostrich". The current study, in addition to clearly revealing the various components of the sperm, demonstrated a distinct difference in cell surface characteristics between the acrosome (smooth) and the rest of the head (nucleus) which appeared mottled.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
See 3 more Smart Citations